Influence of L-carnitine daily supplement on qualitative and quantitative ejaculate indicators in boars during the summer period - Přibilová, Magdalena; Horký, Pavel; Urbánková, Lenka; Nevrkla, Pavel; Skládanka, Jiří (Mendelova univerzita v Brně, 2018)
The purpose of the project was to determine impact of added L-carnitine in feed ration on quality of Duroc boar ejaculate during the summer period (June - September). Temperature in the stable achieved up to 29.9 oC. For the experiment was chosen 24 Duroc boars. Boars were divided into 2 groups: The control group of boars (n = 12) was fed by the basic feed mixture only. The experimental group of boars (n = 12) was supplemented by 500 mg of L-carnitine/kg of the feed ration. Ejaculate was collected once a week. Monitored parameters were: volume of ejaculate, concentration of sperm, total sperm count, motility of sperm and percentage of morphologically abnormal sperm. L-carnitine concentration in the ejaculate was monitored as well. Results of the experiment show that supplementation of 500 g of L-carnitine into boar ration had a positive impact on sperm motility, significant difference between the boar groups by 8.54 % (P < 0.05) and on decreased morphologically abnormal sperm, significant difference between groups by 12.6 % (P < 0.05), and also significant difference in experimental group during the monitoring by 4.06 % (P < 0.05). After biochemical analysis have been found a statistically significant increase in concentration of L-carnitine in the ejaculate of the experimental group (up to 21.1 μg/ml) and a statistically significant difference between groups (22.0 μg/ml), (P < 0.05).
Keywords: Antioxidants; Boar; Ejaculate; L-carnitine